ZAMONAVIY TA’LIMDA CHET TILLARINI O‘RGANISHNING INNOVATSION USULLARI - Usmonova Sayidaxon; Matkarimova Ashurxon (TADQIQOTLAR, 2025)
ABSTRACT: Modern education in language learning is enriched with innovative approaches, enhancing efficiency through digital pedagogy and interactive methods. Online learning platforms expand opportunities for remote education, while AI-based language learning ensures a personalized approach for each learner. These technologies contribute to making the language learning process more convenient, effective, and faster, ultimately improving the quality of education. Innovative methods help strengthen students’ practical skills and increase their level of comprehension. Additionally, these approaches make language learning a more engaging and interactive experience.